Categorical Representation Of Women As The Second Sex: A Sociolinguistic Study Of Hindi Proverbs As Carriers Of Gender Partisanship - Chauhan, Srishti; de Beauvoir, Simone (International Journal of Psychosocial Rehabilitation, 2023)
Language is a perennial part of human existence. Not only is it conducive to our cognitive competence but also renders an insight into its social bearing. It is, therefore, probable for routine concepts to be interpreted differently by speakers of different languages. One such aspect where language influences our consciousness is gender. If gender is continuously asserted in a language, then it could be postulated that employment of that language invariably impacts our thoughts, attitudes and perceptions of women and men. Proverbs in any language serve as reflective tools that impart codified knowledge about a society and its speakers. They are indeed the mirror images of the socio-cultural norms and beliefs of the society in which that language is being spoken. In the context of the present paper, the numerous proverbs available to us in the Hindi language, in all likelihood, are an outcome of observations made about life over the years and imparted across future generations. A profound review, however, of many of these proverbs would reveal how gender prejudice is both lucidly as well as obscurely practiced in everyday discourse and aids our biased conception of gender that is invidious towards women. The hypothesis of linguistic relativity, also known as the Sapir–Whorf hypothesis is the most straightforward sociolinguistic theory in this regard. It puts forward the idea that our thoughts, perceptions and actions are relative to the language we speak. Therefore, the present paper aims at exploring one of the various dimensions of the Hindi language, namely proverbs, with respect to their ability to affect our cognition regarding gender and shape our ideas about femininity and masculinity. Consequently, this paper intends to unveil our skewed cognizance of the female gender by critically examining 10 Hindi proverbs.